2016
DOI: 10.1063/1.4948921
|View full text |Cite
|
Sign up to set email alerts
|

Exchange magnon induced resistance asymmetry in permalloy spin-Hall oscillators

Abstract: We investigate magnetization dynamics in a spin-Hall oscillator using a direct current measurement as well as conventional microwave spectrum analysis. When the current applies an anti-damping spin-transfer torque, we observe a change in resistance which we ascribe to the excitation of incoherent exchange magnons. A simple model is developed based on the reduction of the effective saturation magnetization, quantitatively explaining the data. The observed phenomena highlight the importance of exchange magnons o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 17 publications
5
23
1
Order By: Relevance
“…Furthermore, the value of ∆RUSMR is inverted when the direction of the transverse field is reversed, whereas reversal of the longitudinal field does not influence R||. These symmetries are consistent with the prior studies of USMR, [18][19][20][21][22][23] and mirror those of SHE, indicating a close relationship between these two effects.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the value of ∆RUSMR is inverted when the direction of the transverse field is reversed, whereas reversal of the longitudinal field does not influence R||. These symmetries are consistent with the prior studies of USMR, [18][19][20][21][22][23] and mirror those of SHE, indicating a close relationship between these two effects.…”
supporting
confidence: 88%
“…While the dependence of resistance on the magnetization direction for this effect differs from AMR, both are uniaxial -the resistance is symmetric with respect to the reversal of the magnetization or the current direction. In contrast, the recently discovered unidirectional spin Hall 3 magnetoresistance (USMR) [18][19][20][21][22][23] is determined by the product (j × �) , where j is the density of the electric current, M is the magnetization of the FM layer, and � is the unit vector normal to the plane of the bilayer. Consequently, USMR changes sign when either the magnetization or the electric current is reversed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results reconcile the interpretation of the UMR in terms of spin-dependent conductivity [8,30] and magnon excitations [22,23,26].…”
supporting
confidence: 86%
“…Recent studies have shown that an additional currentdependent unidirectional magnetoresistance (UMR) emerges in FM/NM systems due to either the SHE or REE [8,9,[21][22][23][24][25][26][27]. Unlike the most common magnetoresistive effects, including the anisotropic magnetoresistance (AMR), SMR, and EMR, the UMR is a nonlinear effect that violates Onsager reciprocity, being odd under either magnetization or current reversal.…”
mentioning
confidence: 99%